A proposed model for waqf financing public goods and mixed public goods in Malaysia - Azrai Azaimi Ambrose, Azniza Hartini; Aslam, Mohamed; Hanafi, Hanira (Emerald Publishing Limited, 2018)
Purpose - The purpose of this paper is to formulate a model for waqf financing of public goods and mixed public goods in Malaysia which constitute the country’s federal government expenditures. The model is built on the basis of understanding the concept of waqf, learning from waqf institutions of the past and present and addressing specific Malaysian waqf issues.